Advanced hybrid closed loop on the Polish market - Sebastian Seget; Anna Tekielak; Ewa Rusak; Przemysława Jarosz-Chobot (Termedia Publishing House, 2022)
Since 1921, when Frederick Banting and Charles Best discovered insulin, we have observed rapid development in the field of diabetology. On the one hand, it is associated with clinical research on the aetiopathogenesis of metabolic disorders, and on the other hand, with the development of new technologies such as devices for insulin delivery and glycaemia monitoring. Since December 2020, the Medtronic MiniMed™ 780G system has been available in Poland. This is the first advanced hybrid closed loop personal insulin pump on the domestic market. It uses advanced algorithms to maintain glucose levels at a predetermined threshold by combining information from continuous glucose monitoring, which enables automatic estimation of basal insulin dose and automatic correction combined with manual initiation of meal boluses.